Synergistic modulation of surface interaction to assemble metal nanoparticles into two-dimensional arrays with tunable plasmonic properties - Jiang, Lin (2014)
A simple strategy based on the synergistic modulation of inter-particle and substrate-particle interaction is applied for the large-scale fabrication of two-dimensional (2D) Au and Ag nanoparticle arrays. The surface charge of the substrate is used to redistribute the double layer electric charges on the particles and to modulate the inter-particle distance within the 2D nanoparticle arrays on the substrate. The resultant arrays, with a wide range of inter-particle distances, display tunable plasmonic properties. It can be foreseen that such 2D nanoparticle arrays possess potential applications as multiplexed colorimetric sensors, integrated devices and antennas. Herein, it is demonstrated that these arrays can be employed as wavelength-selective substrates for multiplexed acquisition of surface-enhanced Raman scattering (SERS) spectra. This simple one step process provides an attractive and low cost strategy to produce high quality and large area 2D ordered arrays with tunable properties.